Evaluasi Kepuasan Pengguna Akhir Terhadap Sistem Informasi Akademik (SIAKAD) Universitas Islam Negeri Maulana Malik Ibrahim Malang Menggunakan Metode End-User Computing Satisfaction (EUCS) - Meirina Fatima; Yusi Tyroni Mursityo; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sistem Informasi Akademik (SIAKAD) Universitas Islam Negeri Maulana Malik Ibrahim Malang (UIN Maliki Malang) is an information system used to serve students in UIN which using terchnology. However, in the practicing UIN Maliki Malang get complaints were received by students such as inaccurate scores of students, servers often have problems, less attractive interface, grammar cannot be understand and difficuld for students to use SIAKAD due to the absence of a guidebook. To increase end-user satisfaction, it is necessary to evaluate the end-user of SIAKAD Maliki UIN Malang. This study aims to describe the factors that oppose the End User Computation Satisfaction (EUCS) method towards SIAKAD Maliki UIN Malang which consists of content variables, accuracy, format, ease of use, timeliness, and user satisfaction. This study used a sample of 120 respondents. The analysis used is descriptive statistical analysis. The results of the evaluation indicate that the content of the variable has a value of 3.08 included in the category of satisfaction. While the variables of accuracy has a value of 2.75 included in the category of dissatisfaction, format has a value of 2.90 included in the category of dissatisfaction, ease of use has a value of 2.89 included in the category of dissatisfaction, timeliness has a value of 2.64 included in the category of dissatisfaction, and user satisfaction has a value of 2.89 included in the category of dissatisfaction. Recommendations that can be given to variables included in the category are not satisfied